Soul of Mato - Hishamuddin, Siri; Hafizan, Mohamad Naim; Abdul Walid, Ali (UNIMAS Publisher, 2024)
In 'Soul of Mato', which delves into the mystical beings of Sarawak's Melanau culture. Using digital projection and Al-stable diffusion software, we create a dynamic, immersive experience. The software layers and manipulates traditional Melanau motifs, inviting viewers into a fluid, metaphysical realm. This work bridges ancient lore with modern technology, offering a fresh lens to explore and appreciate Sarawak's rich cultural heritage, It aims to challenge perceptions and foster deeper connection and reflection